Strain and damage self-sensing properties of carbon nanofibers/carbon fiber–reinforced polymer laminates - Wang, Yanlei; Chang, Ruijuan; Chen, Guipeng (Advances in mechanical engineering, 2017)
Unidirectional fiber-reinforced composites of “plain” carbon fiber–reinforced polymer laminates and carbon nanofibers modified carbon fiber–reinforced polymer laminates were prepared based on the manufacture of the epoxy resin modified with various contents of carbon nanofibers. The carbon nanofibers–modified epoxy matrix and carbon fiber–reinforced polymer laminates specimens were subject to constant amplitude cyclic tensile loading, quasi-static tension loading, and incremental cyclic tension loading while the values of their electrical resistance were monitored through electrical resistance technique. Resistance-change curves of carbon nanofibers/carbon fiber–reinforced polymer laminates indicated the changes in conductive percolation networks formed by carbon fibers or carbon nanofibers. These changes can identify the complex damage modes and the loss of mechanical integrity in laminates. The changes in resistance of specimens showed a nearly linear correlation with the strain, so the damage process of the carbon fiber–reinforced polymer laminates can be self-sensed according to the resistance-change curves. In addition, uniformly dispersed carbon nanofibers formed a network that spans the whole insulation area, which improved their self-sensing property of strain sensitivity without compromising the mechanical properties of the carbon fiber–reinforced polymer laminates. This technology can achieve the quantitative strain and damage self-sensing properties of nano-reinforced composites without any additional sensor, and it is bound to be a promising method for in situ health monitoring.